A cautionary (spectral) tail: red-shifted fluorescence by DAPI–DAPI interactions. (9th February 2016) - Omelon, Sidney; Georgiou, John; Habraken, Wouter
Abstract : The fluorescent dye DAPI is useful for its association with and consequent amplification of an ∼460 nm emission maximum upon binding to dsDNA. Labelling with higher DAPI concentrations is a technique used to reveal Pi polymers [polyphosphate (polyP)], with a red-shift to ∼520–550 nm fluorescence emission. DAPI–polyP emissions of ∼580 nm are also generated upon 415 nm excitation. Red-shifted DAPI emission has been associated with polyP and RNA and has more recently been reported with polyadenylic acid (polyA), specific inositol phosphates (IPs) and heparin. We find that amorphous calcium phosphate (ACP) also demonstrates red-shifted DAPI emission at high DAPI concentrations. This DAPI spectral shift has been attributed to DAPI–DAPI electrostatic interactions enabled by molecules with high negative charge density that increase the local DAPI concentration and favour DAPI molecular proximity, as observed by increasing the dye/phosphate ratio. Excitation of dry DAPI (∼360 nm) confirmed a red-shifted DAPI emission. Whereas enzymatic approaches to modify substrates can help define the nature of DAPI fluorescence signals, multiple approaches beyond red-shifted DAPI excitation/emission are advised before conclusions are drawn about DAPI substrate identification.